Traffic routing in telecommunication nets and its diakoptics representation - Klymash, M.; Strykhalyuk, B.; Kaidan, M.; Demydov, I. (Publishing House of Lviv Polytechnic National University, 2011)
Characteristics of flow-oriented models of routing have been classified. The model analysis hascarried out for routing, that is accepted as a basis for the existing telecommunication network protocols. The decomposition representation of telecommunication networks has been performed and a calculation algorithm by diakoptics has been proposed. Класифіковано характеристики потокових моделей маршрутизації. Проведено аналіз моделей маршрутизації, які покладені в основу існуючих протоколів телекомунікаційних мереж. Проведено декомпозиційне представлення телекомунікаційних мереж і запропоновано алгоритм розрахунку методом діакоптики.
Потокова маршрутизація телекомунікаційних мереж і її представлення методом діакоптики
Keywords: diakoptics; tensor; routing; telecommunication networks